The essential guide to studying abroad : from success in the classroom to a fulfilling career - Klassen, Thomas Richard, 1957-; Menges, Christine, 1978- (Routledge, 2020)
"This book is an indispensable how-to-guide on flourishing when studying abroad, and how to use an international education to begin a fulfilling career after graduation. Written in an engaging and accessible style, using many examples, case studies and links to resources, the book reduces the stress of studying abroad. Covering all aspects of the international student experience - inside and outside the classroom - the book encourages young people to perform their very best and succeed in their new environment. International students preparing for cross cultural learning and recent graduates looking for employment will find this book both practical and inspiring"- Resumé vydavatel
Keywords: zahraniční studium; foreign study; elektronické knihy; příručky; electronic books; handbooks and manuals